2002
DOI: 10.1080/13550280260422712
|View full text |Cite
|
Sign up to set email alerts
|

Functional CXCR4 receptor development parallels sensitivity to HIV-1 gp120 in cultured rat astroglial cells but not in cultured rat cortical neurons

Abstract: The alpha chemokine receptor CXCR4 is used as the major coreceptor for the cell entry of T-cell-tropic human immunodeficiency virus-1 (HIV-1) isolates. Activation of this coreceptor by its natural ligand SDF1alpha is associated with an intracellular Ca(2+) increase. Because the HIV-1 glycoprotein 120 (gp120) is shedded from the surface of HIV-1-infected cells and is regarded as an injurious molecule in the pathogenesis of HIV-1-associated encephalopathy (HIVE), we investigated the effects of gp120 on the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Previous studies have shown that the chemokine receptors CXCR4 and CCR5 are expressed in cultured rat astrocytes (Bajetto et al, 1999;Koller et al, 2002). In the present study, we confirmed the expression of both CXCR4 and CCR5 in our primary cultures of rat astrocytes.…”
Section: Chemokine Receptor Gene and Protein Expressionsupporting
confidence: 80%
See 3 more Smart Citations
“…Previous studies have shown that the chemokine receptors CXCR4 and CCR5 are expressed in cultured rat astrocytes (Bajetto et al, 1999;Koller et al, 2002). In the present study, we confirmed the expression of both CXCR4 and CCR5 in our primary cultures of rat astrocytes.…”
Section: Chemokine Receptor Gene and Protein Expressionsupporting
confidence: 80%
“…It is interesting that Kong et al (1996) reported cytokine secretion (i.e., TNF-␣, IL-1␤, and IL-6) in cultured murine astrocytes triggered with subtype B gp120 isoforms. In addition, it has been demonstrated that gp120 may interact with rodent CXCR4 and CCR5 orthologs (Wu et al, 1997;Koller et al, 2002). Therefore, the secretion of cytokines may be facilitated by interactions between shed gp120 and CXCR4/CCR5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV-1 gp120 is able to directly interact with chemokine receptors; for example, X4-gp120 has been shown to mediate signaling in murine and rat cells (3,11,28). Although there are no specific reports that indicate that R5 HIV-1 gp120 can trigger murine CCR5, this protein has been shown to bind this chemokine receptor on rat cells (20).…”
Section: Discussionmentioning
confidence: 99%